Genetic diversity of Hepatozoon (Apicomplexa) from domestic cats in South Africa, with a global reassessment of Hepatozoon felis diversity - D. James Harris; Ali Halajian; Joana L. Santos; Kgethedi Michael Rampedi; Raquel Xavier (2019)
Genetic diversity within partial 18S rRNA sequences from Hepatozoon protozoan parasites from domestic cats in South Africa was assessed and compared against published data to assess global biogeographic patterns. Multiple distinct haplotypes of Hepatozoon felis were identified, as well as an unrelated Hepatozoon lineage. Hepatozoon felis genetic diversity globally is very high, indicating a likely complex of species. The recently described Hepatozoon apri from wild boars is closely related to some lineages of H. felis. Sarcocystis and Babesia parasites were also detected. Since Hepatozoon felis is apparently a species complex, potential differences between genetically distinct forms need to be assessed. The finding of an unrelated Hepatozoon indicates that felids can be infected by more species of Hepatozoonthan currently known, and that trophic interactions may increase the number of Hepatozoon species found in carnivores. Genetic screening again is demonstrated to identify previously unrecognised parasites from vertebrate hosts.